Buttressed and breached: The exurban fortress, cannabis activism, and the drug war's shifting political geography. (August 2020) - Polson, Michael
As the post-1980s revanchist drug war transformed US cities, another spatial formation was materializing: exurbia. The final roost of suburban white flight, exurbia also formed via the spatial–racial dynamics of the drug war. The "exurban fortress" projected an imaginary of urban danger and rural security that (1) solidified an anti-drug constituency among (older, white) property owners and disciplinarily transitioned racially marked and poor white residents from an industrial to postindustrial service economy and (2) ameliorated key contradictions implicit to the production, consumption, and governance of exurbia. Taking the case of Calaveras County, California, this article shows how cannabis prohibition politically stabilized spatial meanings and capital accumulation during a period bookended by recessionary crises in housing production (1992–2010). It also shows how medical cannabis activists reimagined the urban and rural in capacious ways, thus catalyzing a local transformation that mirrored national trends around drugs, penality and Rightist politics. This case illuminates a neglected dimension of drug war geographies and their activist-driven transformation and urges attention to new bordering practices emerging from exurbian spatial imaginaries.